PERCUTANEOUS NEPHROSTOMY FOR RELIEF OBSTRUCTIVE UROPATHY: BENIGN VERSUS MALIGNANT DISEASE - Yuri, Prahara; Rochadi, Sungsang (Indonesian Journal of Urology, 2017)
Objective: This study aimed to find out the effectiveness of percutaneous nephrostomy (PCN) as palliative decompression of the obstructed urinary system. Materials & Methods: A case control study was performed with 118 patients (69 female and 49 male) with obstructive uropathy who were undergoing PCN during 2009 until 2012, retrospectively. The mean of age was 50.03 years. The PCN technique involves an ultrasound-guided puncture of the dilated collecting system with nephrostomy trocar than insert an 8 Fr nasogastric tube as nephrostomy catheter. Differences of renal function between benign and malignancy were assessed using Independent t-test. Changes in renal function after procedure were expressed as mean ± SD and analyzed using Pair t-test.  Results: There was no procedure-related mortality. The most cause of malignancy was cervix cancer (36.4%) while the result of a benign process was 28.8% of urinary tract stones. Dialysis before procedure were performed in 43 (36.4%) consisting of 42 malignancies and 1 benign process. Improvement in renal function were statistically significant both benign and malignant groups seen in the levels of creatinine and blood urea nitrogen (BUN) before and after procedure (p<0.001). The mean differences were also statistically significant at the preoperative creatinine values between benign and malignant processes (p=0.019) but BUN levels before and after as well as postoperative creatinine levels showed no significant difference. Conclusion: PCN is a widely used technique, with a high technical success rate and low rate of complications. Obstructive uropathy due to benign processes had a better prognosis than malignancy after PCN treatment. Hemodialysis was mainly performed in patients with malignancy prior to PCN.